The Argentinean Pampas: A key region with a negative nutrient balance and soil degradation needs better nutrient management and conservation programs to sustain its future viability as a world agroresource - Lavado, Raul Silvio (2009)
The soils of the Pampas region have suffered different processes of degradation and erosion. Several of the causes of this degradation are commonly found throughout the world; other causes are more particular to the Pampas, such as established policies that affected the nutrient balance of the Pampas soils. At present, we face new challenges to maintain nutrient levels and soil productivity of this key world agroecosystem. With continued global population growth, the Pampas region will be an important world resource for grain production. The inherent soil fertility of the region has made this region a major exporter of grains and nutrients until now; however, new nutrient fertility programs will be needed to ensure that the region yield productivity is maintained and/or maximized. Soil and water conservation is a critical component of ensuring the productivity of this world resource, particularly now that carbon sequestration can be used to potentially mitigate anthropogenic emissions of carbon. New policies concerning nutrient management and soil and water conservation will be needed to help maintain the Pampas region as a key world agroecosystem and to provide farmers with viable agroecosystems that maximize productivity and sustainability.